Abortion from an Islamic Ethical Point of View - Demirel, Serdar (Centre for Promoting Ideas (CPI), USA, 2011)
Different nations interact differently with problems based on their different traditional background, interest, as well as their different approaches. But there are issues which need common perspective and the same sense of responsibility in doing good things that concern all such as induced abortion. In this article the researcher analyzed induced abortion from an Islamic ethical point of view with a particular focus on when life right begins.